Investigation of Platinum Nanoparticle Synthesis from Chickpea Extract - Üstünoğlu, Umur; Yetim, Selin; Sarı, Yusuf Mert; Çetiner, Burcu Nilgün (Fırat University, 2025)
Their wide application range in catalysis, electronics, and fuel cells make Platinum Group Metals (PGMs) invaluable and scant raw resources. In this research, nano-scale platinum was extracted from waste platinum coating solutions via a ‘green chemistry’ technique that incorporates chickpea extract. The concentration of the platinum solution ICP-OES confirmed was 125 ppm. Various ratios of the sprouted chickpea extract and pure water were mixed prior to 24 hours of reaction. Zeta potential, UV-VIS spectrophotometry, and nanoparticle size analyses were performed after filtration. The PtCl?²? reduction with confirmed by the UV-VIS absorption peak at 220 nm. The zeta potential analysis showed that the concentration of the nanoparticle increased the potential agglomeration of the nanoparticles increased leading to a lower zeta potential. The SEM-EDS analyses showed the particles to be roughly spherical in shape and around 30 nm in diameter. The FTIR spectroscopy showed that the phenolic and carbonyl groups were attached to platinum. These results prove that the nano-platinum synthesis can successfully be scaled up. Green chemistry and recycling techniques offer a new way of approaching PGM recovery which should be considered further in the future.

Platin Grubu Metaller (PGM), nadir bulunmaları ve kataliz, elektronik, yakıt hücreleri gibi alanlardaki kritik kullanımları nedeniyle önemli hammaddelerdir. Bu çalışmada, yeşil kimya yaklaşımıyla nohut özütü kullanılarak atık platin kaplama çözeltilerinden nano ölçekli platin geri kazanılmıştır. Platin çözeltisinin konsantrasyonun 125 ppm olduğu ICP-OES ile doğrulanmış ve farklı oranlarda nohut filiz özütü ve saf su ilave edilerek 24 saat reaksiyona bırakılmıştır. Ardından, filtrasyon sonrası UV-VIS spektrofotometri, zeta potansiyeli ve nano parçacık boyutu analizleri gerçekleştirilmiştir. UV-VIS sonuçları, PtCl?²?’nin indirgenmesiyle 220 nm’de Pt? absorpsiyon pikini doğrulamıştır. Zeta potansiyeli analizleri, parçacık konsantrasyonunun artışıyla birlikte potansiyelin düştüğünü ve nanopartiküllerin topaklanma eğiliminde olduğunu göstermiştir. SEM-EDS analizleri, parçacıkların küresel formda ve yaklaşık 30 nm boyutunda olduğunu ortaya koymuştur. FTIR spektroskopisi, fenolik ve karbonil gruplarının platine bağlandığını doğrulamıştır. Sonuçlar, biyobazlı indirgeme yöntemlerinin sürdürülebilir nano platin sentezi için etkili bir alternatif sunduğunu göstermektedir. Bu çalışma, yeşil kimya ve geri dönüşüm yöntemleri, PGM geri kazanımı için umut vadeden bir yaklaşım olduğunu göstermektedir.
Nohut Özütünden Platin Nano Parçacık Sentezinin Araştırılması
Keywords: Hydrometallurgy; Hidrometalurji; Environmental and Sustainable Processes; Çevresel ve Sürdürülebilir Süreçler; Metallization and Optimation; Metalleme ve Eniyileme